Methods for building geo-social systems in the internet. Server applications technologies - Shatovska, Tetyana; Kauk, Victor; Vlasenko, Dmytro (Eastern-European Journal of Enterprise Technologies, 2010)
Features of social network services are discussed; the most popular technologies to create such kind of services are listed. Web-service for demonstration of analysis results is reviewed.